Effect of Dietary Canarium indicum L. on the Growth, Health, and Resistance of Asian Seabass Challenged with Vibrio alginolyticus - Taufiq Abdullah; Wahjuningrum, Dinamella; Widanarni Widanarni (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Abstract Canarium indicum offers the potential of usage in aquaculture. This study aimed to evaluate the utilization of C. indicum on growth performance, health, and resistance of Asian seabass Lates calcalifer challenged with Vibrio alginolyticus. The study employed a completely randomized design with seven treatments, namely positive control (K+), negative control (K-), vitamin control (KVit), antibiotic control (KAnt), doses of 5 g kg-1 (D05), 10 g kg-1 (D10), and 20 g kg-1 C. indicum (D20). The test feed was prepared with a coating method and fed for 30 days. On the 31st day of rearing, a challenge test was conducted by injecting V. alginolyticus intramuscularly at 106 CFU mL-1. The results showed that C. indicum treatment for 30 days had a significantly different effect (P<0.05) on weight gain and average daily growth, while KVit and KAnt treatments were not different from the control. After the challenge test, all doses of C. indicum treatment, as well as KVit and KAnt treatments, showed survival significantly different (P<0.05) from that of the positive control, which ranged from 88.89% to 95.56% and was not significantly different (P>0.05) from the negative control. The survival rate condition is identical to the cumulative survival condition which shows the highest mortality found in the positive control. The administration of C. indicum at a dose of 5 g kg-1 to 20 g kg-1 improved the growth performance and prevented V. alginolyticus infection. Highlight Research C. indicum significantly increases the growth of Asian seabass. C. indicum significantly enhances the immune response to V. alginolyticus infection in Asian seabass. C. indicum can prevent V. alginolyticus infection as it resulted in a higher and cumulative survival than the positive control. C. indicum can be developed as an immunostimulant for the prevention of vibriosis in Asian seabass at doses of 5 g kg-1 to 20 g kg-1.